2016
DOI: 10.1002/net.21715
|View full text |Cite
|
Sign up to set email alerts
|

Lightpath admission control and rerouting in dynamic flex‐grid optical transport networks

Abstract: In dynamic flex‐grid optical transport networks, Lightpath Admission Control (LAC) is the task of finding a Routing and Spectrum Assignment (RSA) solution for a current lightpath request; otherwise, the request is blocked if there are not enough free available resources. When rerouting is supported, one or more currently established lightpaths can be rerouted and/or assigned with a different spectrum in order to accommodate the current lightpath request. We propose LAC methods based on mixed integer linear pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 36 publications
(44 reference statements)
0
3
0
Order By: Relevance
“…In large networks the management of the required network resources may be tedious as different NMSs may need to be monitored to keep track of available resources. SDN helps to cut down the use of multiple network EMSs which are usually due to the use of different network equipment from different vendors to a single centralised controller [21]. However, it has been shown that the SDN centralised controller approach suffers from the single point of failure problem [22].…”
Section: Lightpath Admission Controlmentioning
confidence: 99%
“…In large networks the management of the required network resources may be tedious as different NMSs may need to be monitored to keep track of available resources. SDN helps to cut down the use of multiple network EMSs which are usually due to the use of different network equipment from different vendors to a single centralised controller [21]. However, it has been shown that the SDN centralised controller approach suffers from the single point of failure problem [22].…”
Section: Lightpath Admission Controlmentioning
confidence: 99%
“…During the last decade, the attention of the telecommunication community has been concentrated on Routing and Wavelength Assignment (RWA) and Routing and Spectrum Allocation (RSA) problems. Consequently, numerous exact and heuristic methods are now available to solve RWA and RSA problems in static [9][10][11] and dynamic [12][13][14] environment. However, so far the relevance of the inner optical node architecture in the DWDM network optimization has not been fully considered.…”
Section: Introductionmentioning
confidence: 99%
“…De Sousa et al consider dynamic flex‐grid optical transport networks where lightpath (L‐P) admission control (LAC) is the task of finding a routing and spectrum assignment (RSA), if any, for the current L‐P request. When rerouting is supported, one or more currently established L‐Ps can be rerouted and/or assigned a different spectrum in order to accommodate the current L‐P request.…”
mentioning
confidence: 99%